SKRINING BAKTERI PENGHASIL POLI(3-HIDROKSIBUTIRAT) P(3HB) DARI SAMPEL IKAN KEMBUNG (Rastrelliger sp.) - Inayati Rahmi; Anthoni Agustien; Akmal Djamaan (Postgraduate, University of Mataram, 2023)
Bioplastic P(3HB) is a plastic that can be decomposed by decomposing microorganisms. Bacteria can produce P(3HB) in conditions of low nutrition and high carbon sources accumulated in cells as energy reserves. Isolation of bacteria-producing bioplastic P(3HB) was carried out in mackerel fish's gills and intestines, allowing direct contact with polluted waters. This research aimed to determine the presence of P(3HB) bioplastic-producing bacteria in mackerel fish samples and to screen for P(3HB) bioplastic-producing bacteria. The stages of the research were the isolation of P(3HB) producing bacteria from the gills and intestines of mackerel fish, screening of P(3HB) bioplastic-producing bacteria by using Nile Blue A staining, and molecular identification of bioplastic-producing bacteria using 16S rRNA gene. The results of bacterial isolation in the gills and intestines of mackerel obtained 10 bacterial isolates. P(3HB) screening found 1 bacterium showing orange fluorescence, namely IKE-1 isolate which was isolated from the gills of mackerel fish and included in the Gram-negative group with a monobacilli cell shape. Molecular identification of bacteria by using the 16S rRNA gene that isolate IKE-1 is Enterobacter roggenkampii. These results indicate that Enterobacter roggenkampii can produce P(3HB) which was confirmed by the screening results